An Analysis of Language Errors on Students’ Thesis of Business and Economy Syariah Major at UIN Raden Intan Lampung - Dedi Satriawan (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
One of the rules in writing a thesis is using Indonesian language rules properly and correctly. Even though students of the Business and Economy Syariah major focus on writing theses in the field of syariah economics, students are still expected to be able to write theses according to the Indonesian language rules that apply in the guidelines for writing scientific papers issued by institutions related to uniformity and compliance with the rules for writing scientific papers. Classification is used so that analysis of students' language errors can be carried out systematically and not randomly. By classifying these errors, we can determine the grammatical description for each error. Therefore, activities at this stage of classifying errors include determining or determining the grammatical description for each error, for example, (1) errors in the field of phonology, (2) errors in the field of morphology, (3) errors in the field of syntax, and paragraphs. This research was conducted using a qualitative approach, which is included in linguistic research. A qualitative approach was chosen because the problem studied is in the form of data (thesis), which is more precisely explained using words. The results of research on spelling errors in several theses of Business and Economy Syariah major, Faculty of Islamic Economics and Business, UIN Raden Intan Lampung, resulted in 247 cases of errors, which included: (1) errors in the use of capital letters totaling eight errors, (2) errors in the prepositions in and totaling 30 errors, (3) errors in using punctuation totaling 209 cases of errors and (4) Errors in writing absorption elements were not found.